2022
DOI: 10.3390/pharmaceutics14061201
|View full text |Cite
|
Sign up to set email alerts
|

HPMA Copolymer Mebendazole Conjugate Allows Systemic Administration and Possesses Antitumour Activity In Vivo

Abstract: Mebendazole and other benzimidazole antihelmintics, such as albendazole, fenbendazole, or flubendazole, have been shown to possess antitumour activity, primarily due to their microtubule-disrupting activity. However, the extremely poor water-solubility of mebendazole and other benzimidazoles, resulting in very low bioavailability, is a serious drawback of this class of drugs. Thus, the investigation of their antitumour potential has been limited so far to administering repeated high doses given peroral (p.o.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Docetaxel, palbociclib, and angiogenesis-inhibitor were among the extensively used compounds for the treatment of tumor, as determined by their scores. Other drugs/molecules, such as MK-1775 [ 34 , 35 ], MK-5108 [ 36 ], fenbendazole [ 37 , 38 ], albendazole [ 39 ], BAY-K8644 [ 40 ], evodiamine [ 41 ], purvalanol-a [ 42 ], mycophenolic-acid [ 43 ], PHA-793887 [ 44 ], cyclopamine [ 45 ], is a possible treatment for lung adenocarcinoma (Tables 5 , 6 ). To determine the therapeutic potential of these drugs/molecules in patients with lung adenocarcinoma with high EZH2 expression, additional research is necessary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Docetaxel, palbociclib, and angiogenesis-inhibitor were among the extensively used compounds for the treatment of tumor, as determined by their scores. Other drugs/molecules, such as MK-1775 [ 34 , 35 ], MK-5108 [ 36 ], fenbendazole [ 37 , 38 ], albendazole [ 39 ], BAY-K8644 [ 40 ], evodiamine [ 41 ], purvalanol-a [ 42 ], mycophenolic-acid [ 43 ], PHA-793887 [ 44 ], cyclopamine [ 45 ], is a possible treatment for lung adenocarcinoma (Tables 5 , 6 ). To determine the therapeutic potential of these drugs/molecules in patients with lung adenocarcinoma with high EZH2 expression, additional research is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Docetaxel, palbociclib, and angiogenesis-inhibitor were among the extensively used compounds for the treatment of tumor, as determined by their scores. We have identified some potential drugs or molecules for the treatment of lung adenocarcinoma by reading the literature, such as MK-1775 [ 34 , 35 ], MK-5108 [ 36 ], fenbendazole [ 37 , 38 ], albendazole [ 39 ], BAY-K8644 [ 40 ], evodiamine [ 41 ], purvalanol-a [ 42 ], mycophenolic-acid [ 43 ], PHA-793887 [ 44 ], and cyclopamine [ 45 ] (Tables 5 , 6 ). Of interest is the WEE1 inhibitor MK-1775, which has shown potential chemotherapy or radiotherapy sensitivity in preclinical models, particularly, although not exclusively, in p53 mutated or deficient cancer cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gabriele et al showed that the coating of melanin nanoparticles, otherwise known to be biologically benign to human cells with glucose enhanced their uptake with cancer cells cultured in low glucose concentrations, making them more susceptible to killing by laser illumination [ 21 ]. Other original papers published in this Special Issue reported drug delivery systems that have been improved to potentially enhance the effectiveness of complex cancer treatments [ 22 , 23 , 24 , 25 , 26 ].…”
mentioning
confidence: 99%